Strategi Kreatif Tim dalam Iklan Kecap Sedaap di Instagram - Daniel Haposan; Agustrijanto (UNIVERSITAS KALBIS, 2022)
This study aims to explain the creative strategies performed by the creative team Kecap Sedaap for their marketing on Instagram to gain a lot of audience to increase number of consumers is based on the theory of marketing mix that consisted of the Four P (4P) which is product, price, place and promotion. This research method is a case study to study the creative strategy carried out by Kecap Sedaap team from DM Pratama Communication advertising agency which produces advertisements for the Kecap Sedaap Brand. Data were collected through interviews with members of the creative team of graphic design division and Media Planner of the advertising agency. Result of the research shows that the strategy used by the creative team works to gain attentions of the audiences.